2017
DOI: 10.1039/c7nr04656a
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent research on flexible multifunctional nanopapers

Abstract: Traditional paper and papermaking have struggled with a declining market during the last few decades. However, the incorporation of nanotechnology into papermaking has brought possibilities to develop low-cost, biocompatible and flexible products with sophisticated functionalities. The functionality of nanopapers emerges from the intrinsic properties of the nanofibrous network, the additional loading of specific nanomaterials (NMs), or the additional deposition and patterning of thin films of nanomaterials on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 214 publications
3
83
0
2
Order By: Relevance
“…Also, paper is cheaper and withstands thermal annealing or sintering used in R2R printing better [7]. However conventional paper products have a highly porous and rough surface, are hygroscopic, and have low resistance to high temperature and heat that complicates the fabrication of flexible devices [25] [33]. As a result, to control and improve paper's permeability, strength, smoothness and optical characteristics, it is often loaded with various additives, like binders, fillers and pigments [7].…”
Section: Printing Substratesmentioning
confidence: 99%
“…Also, paper is cheaper and withstands thermal annealing or sintering used in R2R printing better [7]. However conventional paper products have a highly porous and rough surface, are hygroscopic, and have low resistance to high temperature and heat that complicates the fabrication of flexible devices [25] [33]. As a result, to control and improve paper's permeability, strength, smoothness and optical characteristics, it is often loaded with various additives, like binders, fillers and pigments [7].…”
Section: Printing Substratesmentioning
confidence: 99%
“…Such papers, also called nanopapers, have unique properties such as elevated strain resistance, biodegradability, 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 hydrophobicity, conductivity, magnetism, and bioactivity that incorporate the functionality of a nanoparticle into cellulose paper. [156] This area was recently reviewed by Dufresne et al, [157] who described several preparation procedures, properties and emerging electronic and electrochemical applications such as use of these materials in batteries, supercapacitors, [158] fuel cells, flexible electronics, and sensing, biomedical and healthcare applications. Another recent review, by Merkoçi et al, [159] showed the use of nanocellulose in its various forms for sensing and biosensing applications, including several uses of nanocellulose papers in POC analysis.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…In particular, cellulose nanopaper has received a high attention during the past decade for its clean manufacture and its outstanding optical, thermal, and mechanical properties [14] and for its compatibility with printing technologies [15]. Its transparency, combined with the above mentioned features, has increased the interest towards cellulose nanopaper, attracting the attention of the scientific and industrial communities, especially as substrate for optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%